TEST FORMULAS AND HEDONIC LIPCREAM CHOCOLATE SEED EXTRACT (THEOBROMA CACAO L.) - Bayu Herdi Alhuda; Rizki Rahmah Fauzia; Rachma Ghiztha Setiawan; Yoga Nugraha (International Journal Labs, 2022)
Cocoa bean (Theobroma cacao L.) contain anthocyanins which can be used as natural dyes. The purpose of this study was to determine whether lip cream preparations with natural dyes cocoa bean extract (Theobroma cacao L.) met the requiretments for good and stable lip cream quality during storage. The method used in this study using the experimental method. This research was made with 3 concentrations, namely lip cream-colored cocoa bean extract (Theobroma cacao L.) with a concentrations of 6% (X1), 10% (X2), and 14% (X3). Cocoa bean extrack was obtained using the maceration method with etanol 70% and acetic acid 2% as solvents. Evaluation was carried out on all formulas including organoleptic test, homogenity test, spreadability test, spreadability test, adhesion test, pH test, stability test, and hedonic test. The lip cream is creamy in color and has a distinctive smell and is unstable in storageCocoa Bean Extract (Theobroma cacao L.), maceration, Lip cream.